Recognizing and Responding to the "Toxic" Work Environment: Worker Safety, Patient Safety, and Abuse/Neglect in Nursing Homes. (October 2017) - Pickering, Carolyn E. Z.; Nurenberg, Katie; Schiamberg, Lawrence
This grounded theory study examined how the certified nursing assistant (CNA) understands and responds to bullying in the workplace. Constant comparative analysis was used to analyze data from in-depth telephone interviews with CNAs ( N = 22) who experienced bullying while employed in a nursing home. The result of the analysis is a multistep model describing CNA perceptions of how, over time, they recognized and responded to the "toxic" work environment. The strategies used in responding to the "toxic" environment affected their care provision and were attributed to the development of several resident and worker safety outcomes. The data suggest that the etiology of abuse and neglect in nursing homes may be better explained by institutional cultures rather than individual traits of CNAs. Findings highlight the relationship between worker and patient safety, and suggest worker safety outcomes may be an indicator of quality in nursing homes.